2019
DOI: 10.1007/jhep05(2019)187
|View full text |Cite
|
Sign up to set email alerts
|

Phases of 5d SCFTs from M-/F-theory on non-flat fibrations

Abstract: We initiate the systematic investigation of non-flat resolutions of non-minimal singularities in elliptically fibered Calabi-Yau threefolds. Compactification of M-theory on these geometries provides an alternative approach to studying phases of five-dimensional superconformal field theories (5d SCFTs). We argue that such resolutions capture non-trivial holonomies in the circle reduction of the 6d conformal matter theory that is the F-theory interpretation of the singular fibration. As these holonomies become m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(134 citation statements)
references
References 120 publications
0
134
0
Order By: Relevance
“…A further set of constraints, which we refer to as the "constraints on the number of hypermultiplets", comes from the analysis of single gauge node quivers in [9]. In that paper it was shown that if a 5d single gauge node quiver was to lead to an interacting SCFT in the UV then the matter content (and where relevant the Chern-Simons level) must satisfy the 12 We remind the reader that by a "pure-gauge" quiver we mean a quiver consisting only of gauge nodesthere remain bifundamental matter fields between these gauge nodes. 13 For low ranks these constraints will, in fact, generally be enough to completely fix Qs.…”
Section: Constraints On Quiver Gauge Theoriesmentioning
confidence: 99%
See 3 more Smart Citations
“…A further set of constraints, which we refer to as the "constraints on the number of hypermultiplets", comes from the analysis of single gauge node quivers in [9]. In that paper it was shown that if a 5d single gauge node quiver was to lead to an interacting SCFT in the UV then the matter content (and where relevant the Chern-Simons level) must satisfy the 12 We remind the reader that by a "pure-gauge" quiver we mean a quiver consisting only of gauge nodesthere remain bifundamental matter fields between these gauge nodes. 13 For low ranks these constraints will, in fact, generally be enough to completely fix Qs.…”
Section: Constraints On Quiver Gauge Theoriesmentioning
confidence: 99%
“…To begin with, we briefly recall the necessary background material on non-minimal singularities in elliptic fibrations, their (possibly non-flat) resolutions, and their role in engineering 5d SCFTs, and refer to [2,12] for more details.…”
Section: Fibers From Coulomb Branch Phasesmentioning
confidence: 99%
See 2 more Smart Citations
“…As many of such 5d N = 1 theories can be engineered via Type IIB 5-brane webs [12,13] or M-theory on Calabi-Yau (CY) threefold [14,15], brane configurations also provide a direct description of the prepotential. For instance, one can study CY geometry of 5d gauge theories to obtain their triple intersections which yield the prepotential of the 5d theories or one can also scan possible gauge theory descriptions from the geometry which lead to a classification of the UV-dual theories [6,9,11,[16][17][18][19]. Though Type IIB 5branes can be understood as dual description of the geometry, not all CY geometries can be realized as a 5-brane web.…”
Section: Introductionmentioning
confidence: 99%